2014
DOI: 10.1158/1055-9965.epi-14-0102
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Extremely Low-Frequency Magnetic Fields and Brain Tumor Risks in the INTEROCC Study

Abstract: Background Occupational exposure to extremely low frequency magnetic fields (ELF) is a suspected risk factor for brain tumours, however the literature is inconsistent. Few studies have assessed whether ELF in different time windows of exposure may be associated with specific histologic types of brain tumours. This study examines the association between ELF and brain tumours in the large-scale INTEROCC study. Methods Cases of adult primary glioma and meningioma were recruited in seven countries (Australia, Ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 35 publications
0
51
0
Order By: Relevance
“…Finally, participation rates were low, ranging from 68% to 81% in cases to 50% in controls. Though participation may be related with socioeconomic and employment status,46 level of educational attainment and occupational prestige (based on the standard international occupational prestige scale) were generally similar across groups of interviewed participants here 28. The somewhat lower participation rate for glioma as compared with meningioma cases was expected due to the severity of disease and poorer prognosis.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Finally, participation rates were low, ranging from 68% to 81% in cases to 50% in controls. Though participation may be related with socioeconomic and employment status,46 level of educational attainment and occupational prestige (based on the standard international occupational prestige scale) were generally similar across groups of interviewed participants here 28. The somewhat lower participation rate for glioma as compared with meningioma cases was expected due to the severity of disease and poorer prognosis.…”
Section: Discussionmentioning
confidence: 65%
“…In the international INTEROCC study, a large-scale, population-based, case–control study including data on nearly 2000 cases of both glioma and meningioma, based on the larger INTERPHONE study, we recently reported no association between lifetime cumulative ELF exposure and glioma or meningioma risk, although positive associations with ELF were noted in the most recent ETW, 1–4 years prior to the diagnosis/reference date (OR≥90th percentile vs <25th percentile for glioma=1.67, 95% CI 1.36 to 2.07; for meningioma=1.23, 95% CI 0.97 to 1.57) possibly suggesting an aetiological role of ELF in brain tumour promotion or progression 28. Although there was no clear evidence for associations between occupational exposure to combustion products, dusts and other chemical agents29 or solvents30 and either glioma or meningioma risk in INTEROCC, we recently observed evidence for positive associations between occupational metal exposures, particularly iron exposure in women, as well as oil mist exposure overall, and meningioma risk (Ref.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Additional analyses found inconsistent evidence for an association between the use of synthetic hair dye and meningioma6 and an association between meningioma and herbicide or insecticide exposure among women, but not in men 7. A French population-based case-control study concluded that meningioma may be caused by occupational or residential exposure to electromagnetic fields,8 although the evidence in support of an association with occupational exposure from the INTEROCC international study was somewhat weaker 9. No association was found between mobile phone use and meningioma 10 11.…”
Section: Introductionmentioning
confidence: 99%